How to measure financial (in)stability in emerging Europe? - Petr Jakubík; Tomáš Slačík (Charles University in Prague, Institute of Economic Studies (IES), 2013)
The importance of assessing financial stability in emerging Europe has increased rapidly since the recent financial crisis. Against this background, in the present paper we contribute to the existing literature in a twofold way: First, by using a broad range of indicators from money, bond, equity and foreign exchange markets, we develop a comprehensive financial instability index (FII) that gauges the level of financial market stress in some key Central, Eastern and Southeastern European (CESEE) countries. In a second step, we perform a panel estimation to investigate which macroprudential indicators that cover both internal and external imbalances explain the evolution of our FII over the past more than 15 years. Our analysis suggests that both the levels and changes of some indicators (such as credit growth and the level of private sector indebtedness) play an important role for financial stability. Moreover, we find that the impact of some key indicators on financial (in)stability is nonlinear and varies over time depending on market sentiment.
Keywords: G28; G32; G33; G38; 330; financial stability; crisis; macroprudential framework; emerging Europe; external and internal imbalances